The 2-modular decomposition matrices of the non-principal blocks of maximal defect of the triple cover of the sporadic simple McLaughlin group - Hiss, Gerhard; Lux, Klaus; Müller, Jürgen (Journal of symbolic computation, 1995)
The calculation of the modular character tables of 3.McL is completed by the determination of the 2-modular decomposition numbers of the faithful irreducible ordinary characters of 3.McL. The results are obtained by using the computer algebra systems MOC, Meat-Axe and GAP, and by applying condensation methods.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 22.05.2023